Therapeutic politics: critique and contestation in the post-political conjuncture - Suvi Salmenniemi (Routledge, 2022)
This article addresses forms of political engagement in the therapeutic field. Drawing on ethnographic research on popular psychology self-help, alternative and complementary health practices and new spiritualities, the paper takes issue with the dominant interpretation of the therapeutic as a depoliticizing force. Although this interpretation captures important facets of the phenomenon, the paper suggests that something more complex is afoot. It argues that therapeutic practices may also animate political contestation and critique, and challenge the prevailing grammar of political conflict. It substantiates this argument by identifying two modalities of politics in the therapeutic field: collective mobilization through a political party, and therapeutic practices as a form of lifestyle politics. It goes on to suggest that, together, these modalities constitute a subaltern counterpublic politicizing the political economy of health and the erosion of democratic governance. The paper concludes by suggesting that analysis of the therapeutic field may shed light on the shifting logics of political contestation at the contemporary political conjuncture.